2019
DOI: 10.1088/1742-5468/ab47fb
|View full text |Cite
|
Sign up to set email alerts
|

Correlations and transport in exclusion processes with general finite memory

Abstract: We consider the correlations and the hydrodynamic description of random walkers with a general finite memory moving on a d dimensional hypercubic lattice. We derive a drift-diffusion equation and identify a memory-dependent critical density. Above the critical density, the effective diffusion coefficient decreases with the particles' propensity to move forward and below the critical density it increases with their propensity to move forward. If the correlations are neglected the critical density is exactly 1/2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 91 publications
2
10
0
Order By: Relevance
“…Whilst our analysis yields a diffusivity linear in the density u for both one and two dimensions, the analogous result for diffusivity in one dimension obtained by Teomy and Metzler [26] varies quadratically with density. In particular, the authors reported a critical density (1/2 in the mean-field approximation), below which the diffusivity increases with increasing persistence, and above which the diffusivity instead decreases with increasing persistence.…”
Section: A Single Speciessupporting
confidence: 81%
See 4 more Smart Citations
“…Whilst our analysis yields a diffusivity linear in the density u for both one and two dimensions, the analogous result for diffusivity in one dimension obtained by Teomy and Metzler [26] varies quadratically with density. In particular, the authors reported a critical density (1/2 in the mean-field approximation), below which the diffusivity increases with increasing persistence, and above which the diffusivity instead decreases with increasing persistence.…”
Section: A Single Speciessupporting
confidence: 81%
“…For the basic case of a single species of motion-persistent agents, we find that such systems are approximately governed by nonlinear diffusion equations. Although our analysis yields results resembling those presented by Teomy and Metzler [26], key differences are revealed regarding the descriptions of population-level behaviour. We extend our analysis to consider generalisations of the basic model involving multiple species of interacting agents as well as a superimposed global drift effect, showing that in general such systems are approximately governed by systems of nonlinear advection-diffusion equations.…”
Section: Arxiv:190710795v2 [Physicsbio-ph] 16 Sep 2019supporting
confidence: 66%
See 3 more Smart Citations